1982
DOI: 10.1128/jcm.15.5.761-768.1982
|View full text |Cite
|
Sign up to set email alerts
|

Serotyping of Campylobacter jejuni by slide agglutination based on heat-labile antigenic factors

Abstract: A serotyping scheme for Campylobacter jejuni was developed based on slide agglutination of live bacteria with whole cell antisera absorbed with homologous heated and heterologous unheated cross-reactive antigens. Among 815 isolates from human and nonhuman sources, 21 serogroups were recognized. Of the 615 isolates from human cases of gastroenteritis, 529 (86%) were typable; 455 strains agglutinated in 20 single antisera, whereas 74 isolates agglutinated in various pairs of antisera, allowing subdivision of som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
137
2
3

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 408 publications
(143 citation statements)
references
References 25 publications
1
137
2
3
Order By: Relevance
“…Serotyping, based on heat-labile antigens (HL) (Lior et al, 1982) or heat-stable antigens (HS) (Penner and Hennessy, 1980), and phagetyping (Grajewski et al, 1985;Frost et al, 1999;Patton et al, 1991) have been the main phenotypic methods applied separately or in combination. As well as being technically demanding, poor and variable typeability (the proportion of isolates for which a subtype can be determined) is inherent to the serotyping methods applied to C. jejuni .…”
Section: Laboratory Methods Of Phenotypingmentioning
confidence: 99%
“…Serotyping, based on heat-labile antigens (HL) (Lior et al, 1982) or heat-stable antigens (HS) (Penner and Hennessy, 1980), and phagetyping (Grajewski et al, 1985;Frost et al, 1999;Patton et al, 1991) have been the main phenotypic methods applied separately or in combination. As well as being technically demanding, poor and variable typeability (the proportion of isolates for which a subtype can be determined) is inherent to the serotyping methods applied to C. jejuni .…”
Section: Laboratory Methods Of Phenotypingmentioning
confidence: 99%
“…Reports from industrialised countries, including European countries [19][20][21]24,[30][31][32][33], Canada [34] and the USA [35], and from developing countries, including Zaire [23] and Rwanda [36], have shown that Campylobacter enteritis occurs worldwide. In 1979, the first full account of Campylobacter enteritis in man was published [37], and in the 1980s Penner and Hennessy [38] and Lior et al [39] described serotyping techniques that, aided by biotyping, phage typing and genotyping, still form the basis of strain typing. It was not until the mid-1980s that C. jejuni was recognised as the most frequent cause of bacterial enterocolitis in man.…”
Section: The Breakthroughmentioning
confidence: 99%
“…It is also well established that the¯agellar antigen contributes signi®cantly to antigenic diversity among strains of C. jejuni, although not in H. pylori. The antigenic diversity in C. jejuni¯agella is thought to be the main active element in the typing scheme utilizing heat-labile antigens known as the Lior scheme (Lior et al 1982). Molecular data support this view; agellin sequences show that there is considerable interstrain diversity, especially in the central region of the FlaA¯agellin proteins, and indeed¯agellin gene polymorphisms have also been proposed as a basis for molecular typing.…”
Section: Flagella As Antigensmentioning
confidence: 97%